Sitophilus granarius L. (Coleoptera) Toxicity and Biological Activities of the Essential Oils of Tanacetum macrophyllum (Waldst. & Kit.) Schultz Bip. - Polatoglu, Kaan; Karakoc, Omer Cem; Demirci, Betul; Goren, Nezhun; Baser, Kemal Huesnue Can (JAPAN OIL CHEMISTS SOC, 2015)
Insecticides of the natural origin are an important alternative to the synthetic insecticides that are being employed for the preserving stored products. The volatiles obtained from T. cinerariifolium (=Pyrethrum cinerariifolium) is being used for many types of insecticidal applications; however there is a very little information on the insecticidal activity of the essential oils of other Tanacetum species. The main purpose of the present study is to determine the chemical composition of T. macrophyllum (Waldst. & Kit.) Schultz Bip. essential oils and evaluate their insecticidal activity against S. granarius as well as its other beneficial biological activities. Highest contact toxicity was observed in the leaf oil of (88.93%) against S. granarius. The flower oil showed considerable fumigant toxicity against L. minor at 10 mg/mL application concentration (61.86 %) when compared with other samples at the same concentration. The highest DPPH (2,2-Diphenyl-1-picrylhydrazyl) scavenging activity (47.7%) and phosphomolybdenum reducing activity was observed also for the flower oil of T. macrophyllum at 10 mg/mL concentration. The essential oils were analyzed by GC, GC/MS. The flower and leaf oils were characterized with gamma-eudesmol 21.5%, (E)-sesquilavandulol 20.3%, copaborneol 8.5% and copaborneol 14.1%, 1,8-cineole 11%, bornyl acetate 9.6%, borneol 6.3% respectively. AHC analysis of the qualitative and quantitative data obtained from the essential oil composition of the E macrophyllum essential oil from the present research and previous reports pointed out that two different chemotypes could be proposed with current findings which are p-methyl benzyl alcohol/ cadinene and eudesmane chemotypes.
Keywords: Tanacetum macrophyllum; essential oil; Sitophilus granarius toxicity; HPTLC-PRAP activity; chemotype; ENANTIOMERIC DISTRIBUTION; BOTANICAL INSECTICIDES; ANTIBACTERIAL ACTIVITY; ANTIMICROBIAL ACTIVITY; ANTIOXIDANT ACTIVITY; MAJOR COMPONENT; VULGARE; CHILIOPHYLLUM; ANTIFEEDANT; ARGENTEUM; Chemistry; Food Science & Technology